The ATP required for potentiation of skeletal muscle contraction is released via pannexin hemichannels - Riquelme, Manuel A.; Cea, Luis A.; Vega, José L.; Boric, Mauricio P.; Monyer, Hannah; Bennett, Michael V. L.; Frank, Marina; Willecke, Klaus; Sáez, Juan C. (Neuropharmacology, 2013)
During repetitive stimulation of skeletal muscle, extracellular ATP levels raise, activating purinergic receptors, increasing Ca2+ influx, and enhancing contractile force, a response called potentiation. We found that ATP appears to be released through pannexin1 hemichannels (Panx1 HCs). Immunocytochemical analyses and function were consistent with pannexin1 localization to T-tubules intercalated with dihydropyridine and ryanodine receptors in slow (soleus) and fast (extensor digitorum longus, EDL) muscles. Isolated myofibers took up ethidium (Etd+) and released small molecules (as ATP) during electrical stimulation. Consistent with two glucose uptake pathways, induced uptake of 2-NBDG, a fluorescent glucose derivative, was decreased by inhibition of HCs or glucose transporter (GLUT4), and blocked by dual blockade. Adult skeletal muscles apparently do not express connexins, making it unlikely that connexin hemichannels contribute to the uptake and release of small molecules. ATP release, Etd+ uptake, and potentiation induced by repetitive electrical stimulation were blocked by HC blockers and did not occur in muscles of pannexin1 knockout mice. MRS2179, a P2Y1R blocker, prevented potentiation in EDL, but not soleus muscles, suggesting that in fast muscles ATP activates P2Y1 but not P2X receptors. Phosphorylation on Ser and Thr residues of pannexin1 was increased during potentiation, possibly mediating HC opening. Opening of Panx1 HCs during repetitive activation allows efflux of ATP, influx of glucose and possibly Ca2+ too, which are required for potentiation of contraction. This article is part of the Special Issue Section entitled ‘Current Pharmacology of Gap Junction Channels and Hemichannels’.
Gesehen am 14.01.2022